AB0382 Factors Associated with the Incidence of Infusion Reactions to Infliximab: Results from "Remitrac Infusion", A Prospective Real-World Community Registry. (10th June 2014) - Choquette, D.; Bensen, W.J.; Faraawi, R.; Nantel, F.
Abstract : Background: Infliximab (IFX) is a therapeutic monoclonal antibody targeting TNFa indicated in the treatment of a number of chronic inflammatory diseases. IFX is administered by intravenous infusion and may be associated with infusion reactions (IRs). RemiTRAC Infusion was a prospective observational registry conducted in 12 Canadian sites from 2005-2012. Objectives: The primary objective of this registry was to describe the types and frequency of IRs to IFX and access factors potentially associated with their incidence. Methods: An IR was defined as any AE occurring during the infusion or within 1 hour post-infusion. The primary endpoint was to access factors potentially associated with the incidence of infusion reactions using multilevel logistic regression analysis. Another major secondary endpoint was to assess the effect of pre-infusion medications and concomitant medications on infusion reactions by propensity score adjusted analysis using a Multilevel logistic regression model with the following variables as predictors: Patient age, weight and gender; prior enrolment use of IFX, any prior biologic use; indication; season and year of infusion; patient eligibility; dose; time since the last infusion and number of previous IRs. Results: 1632 patients were enrolled and 24, 852 infusions were recorded. The majority (63%) of patients in this cohort are treated with IFX for rheumatologic conditions such as RA (40%), AS (18%) and PsA (6%). 201/1632 (12.3%) patients reported at least one IR. Of 24, 852 infusions, 322 resulted in an IR (1.3%) and most IRs were mild to moderate in severity (95%). The most common IR was pruritus, occurring in 19.9% of infusion reactions. Flushing (9.9%) and dyspnoea (6.2%) are the only other infusion AEs occurring in ≥5% of IRs. Four serious IRs (fever, itching/flushing, chest pain, chest pain/flushing) and no serious anaphylactic reactions occurred. Multivariate analysis showed that the use of antihistamines as pre-treatment (2.49% vs 1.32%; p<0.0001), number of previous IRs (O.R. 2.04; p<0.001), female gender (2.21% vs 1.49%; p<0.0011), and corticosteroids before enrolment (p=0.0003) were significantly associated with an increase incidence of IRs. There was a negative association with the year of administration (O.R. 0.68; p<0.0001) which could reflect the improved experience of sites over time. Propensity score adjusted analysis showed that the use of any concomitant immunosuppressant or corticosteroids did not influence the incidence of IRs. Anti-histamines (O.R. 1.58; p=0.0007) and steroids (O.R. 1.50; p=0.0057) were associated with an increased incidence of IRs and only the use of acetaminophen monotherapy was associated with a significant reduction in the incidence of IRs (O.R. 0.61; p=0.0426). Conclusions: This registry shows that in community-based infusion clinics, IR to IFX are uncommon and largely mild to moderate in nature. Anti-histamines, intravenous steroids and acetaminophen have been widely used as preventative medication but data shown in this registry demonstrate a lack of benefit. Indeed the use anti-histamines was associated with an elevated incidence of IRs. Disclosure of Interest: D. Choquette Grant/research support: Janssen, W. Bensen Consultant for: Janssen, R. Faraawi: None declared, F. Nantel Employee of: Janssen DOI: 10.1136/annrheumdis-2014-eular.3672